Sidebend world - Webb, Charles Harper (Pitt poetry series., 2018)
Sidebend World shows clearly why Webb has been called one of the most inventive, incisive, and psychologically astute poets writing in the U.S.A. today, as well as one of the most entertaining. Webb is celebrated for his use of humor; yet even his funniest poems rise, as the best humor must, from serious concerns. Powered by an uncompromising but compassionate intelligence and an abiding wonder at the beautiful strangeness of the world, Sidebend World explores with clarity and vividness a wide range of emotions--love to hate, tenderness to brutality; yet, above all, Webb is a poet of praise. Metaphors of startling aptness and originality, a distinctive voice at once provocative and endearing, high musicality, propulsive energy, wild imaginative leaps, as well as mastery of diction from lyricism to street-speak, create a reading experience of the first order. These poems go down easy, but pack a wallop. As Robert Frost said poetry should do, Sidebend World "begins in delight and ends in wisdom."